DEAPS-An Alternative to DMAIC? – A Case Study - Bishu, Ram R; Jones, Erick C; Thummalapalli, Rama (International Journal of Industrial Engineering: Theory, Applications and Practice, 2009)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; text-autospace:none; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> “To provide leadership in the promotion and protection of the health and social well being of the community through advocacy, education and community-based health services” is a sample mission statement of a prominent Department of Health and Human Services in large metropolitan city. Creating an effective, innovative and modern Information Technology (IT) division driven strategy to support hardware, desktop software, and health department applications which are specifically aligned to goals of health department programs is a necessary but daunting task for management. A strategy based on Lean tools and a revised Six Sigma approach, DEAPS was created to implement Integrated Health Care Systems (IHCS) and the results were demonstrated in a public health and human services department. Discussion includes an economic analysis to demonstrate how health care operations can be enhanced with the implementation of IHCS. <!--EndFragment-->